Education Cost in Elementary Schools: A Case-Study of SDIT Persis dan SDN Sukamentri 7 - Basri, Junaidin; Rohim, Saepul; Jubaedah, Endah (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Education cost planning is essential for ensuring the sustainability and quality of elementary education, particularly amid differences in funding capacity between public and private schools. In Indonesia, the School Revenue and Expenditure Budget Plan (RAPBS/RKAS) serves as a key instrument for managing education financing and strengthening school resilience. This study aims to 1) examine elementary schools’ ability to plan education costs based on the RAPBS/RKAS and 2) analyze the impact of budget planning implementation on school resilience in sustaining educational services. Using a descriptive qualitative approach with a case-study design, the research was conducted in two elementary schools—a public school and a private Islamic integrated elementary school (SDIT). Data were collected through interviews, RAPBS/RKAS document analysis, and observations, and analyzed thematically. The findings show that both schools generally apply education cost planning principles as reflected in their RAPBS/RKAS. However, significant differences are evident in funding sources and budget allocation patterns. The SDIT relies primarily on community and parental contributions, while the public school depends largely on government funding, with the largest share allocated to teacher and education personnel salaries. These differences influence schools’ financial resilience and sustainability. The study highlights the need for adaptive and diversified education financing policies at the elementary level.